Pengaruh Kecerdasan Emosional, Lingkungan Kerja Dan Beban Kerja Terhadap Stres Kerja (Studi pada PR DD Tajinan Malang) - Muflih Abdur Rohman; Agus Widarko; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research aims to determine and analyze the influence of emotional intelligence, work environment and workload on work stress. This research uses a population and sample of PR DD Tajinan Malang employees, totaling 47 respondents. Questionnaires were used as a data collection method. The data analysis methods used in this research are Instrument Test (validity test and reliability test), Normality Test, Classic Assumption Test (multicollinearity test and heteroscedasticity test), Multiple Linear Regression Analysis, Hypothesis test (F test and t test), and Test Coefficient of Determination (Adjusted R2). The analysis process uses SPSS. The research results state that Emotional Intelligence, Work Environment, and Workload have a significant effect on Job Stress. Emotional Intelligence has a significant effect on Job Stress. The work environment has a significant effect on work stress. Workload has a significant effect on Job Stress. Keywords: Emotional Intelligence, Work Environment and Workload on Job Stress